Augmented Reality Application Development using Unity and Vuforia - János Simon (Interdisciplinary Description of Complex Systems, 2023)
This article presents a method to develop an application based on Augmented Reality technology in a Unity development environment. The article presents two test scenarios that give an insight into the possibilities of augmented reality applications. The first scenario is a presentation of a simple game based on a graphic marker and its generated content in the form of a maze. By physically moving the marker in front of the camera, the maze and the ball inside is moved. The second scenario includes a simulation environment of a collaborative robot in the form of an augmented reality application that offers the possibility of planning the robot's trajectories. The possibilities of this technology are endless and cover a large segment of application development from educational to industrial applications. Marker based Augmented Reality using predefined visual markers embedded within the system, physical world objects are detected for superimposition of virtual elements. The test application was designed using a combination of Vuforia, Unity 3D platforms, and the mobile phone used was an Android based Xiaomi Redmi 10 pro phone. This article focuses on the implementation challenges faced whilst designing Augmented Reality applications on mobile platforms.